The Whys and Wherefores of Transitivity in Plants - de Felippes, Felipe F.; Waterhouse, Peter M. (Frontiers in Plant Science, 2020)
Transitivity in plants is a mechanism that produces secondary small interfering RNAs (siRNAs) from a transcript targeted by primary small RNAs (sRNAs). It expands the silencing signal to additional sequences of the transcript. The process requires RNA-dependent RNA polymerases (RDRs), which convert single stranded RNA targets into a double stranded (ds) RNA, the precursor of siRNAs and is critical for effective and amplified responses to virus infection. It is also important for the production of endogenous siRNAs, such as phased siRNAs (phasiRNAs), which regulate several genes involved in development and adaptation. Transitivity on endogenous transcripts is very specific, utilizing special primary sRNAs, such as miRNAs with unique features, and particular ARGONAUTEs. In contrast, transitivity on transgene and virus (exogenous) transcripts is more generic. This dichotomy of responses implies the existence of a mechanism that differentiates self from non-self targets. In this work, we examine the possible mechanistic behind the dichotomy and the intriguing counter-intuitive directionality of transitive sequence-spread in plants.